Aplikasi Pembelajaran Interaktif berbasis Android pada Mata Pelajaran Informatika - Fahrur Rozi; Ellyfiana Nikmahtus Sholikah (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
The use of smartphone technology among students has not been utilized properly, because it is only used for entertainment. This is one of the factors inhibiting learning due to excessive use of smartphones so that it consumes learning time, especially in informatics subjects, so a learning media is needed in the form of an android-based interactive learning application. This study aims to develop interactive learning media and determine the feasibility level of the application. The research method used is research and development (R&D) with the R2D2 development model (Reflective, Recurcive, Design and Development) which has 3 main focuses, namely the focus of determination, the focus of determining design and development, and the focus of dissemination. The data collection methods used are interviews and distributing questionnaires which are then analyzed by calculating percentages based on the level of media feasibility which will be converted to a feasibility scale. The results of the first data analysis were carried out to media experts who got a result of 78% and entered the feasible category, the second test was carried out by material experts and got a percentage of 90% and entered the very feasible category, the third test was carried out to a small group and got a percentage of 92% and entered the very feasible category, and the last test carried out to a large group got a percentage of 92.5% with conversion to a feasible scale.